PENGARUH PENDAPATAN ASLI DAERAH DAN DANA PERIMBANGAN TERHADAP PENGALOKASIAN ANGGARAN BELANJA MODAL - Lestari, Winda Putri; Sapari, Sapari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTLocal own source revenue and equalization fund the sources of local government revenue. The existence of local own source revenue and equalization fund has made the local government is required to use these funds as efficient as possible and to realize these funds through beneficial development and give satisfaction for community on their own environment. The purpose of this research is to test the influence of local own source revenue and equalization fund to the Allocation of Local Capital Expenditure Budget. The population is all Local Government of districts / cities in East Java Province in 2012-2015 fiscal years. The data is the secondary data which has been obtained from the Audit Board of the Republic of Indonesia East Java Province Representative in the form the result of financial audit report of districts / cities in East Java Province in 2012-2015 fiscal years. The data analysis instrument has been carried out by using multiple linear regressions analysis. Based on the result of the test, it shows that (1) local own source revenue gives positive and significant influence to the Allocation of Local Capital Expenditure Budget of districts / cities in East Java Province in 2012-2015 fiscal years, (2) equalization fund give positive and significant influence to the Allocation of Local Capital Expenditure Budget of districts / cities in East Java Province in 2012-2015 fiscal years.Keywords: Local own source revenue, equalization fund, capital expenditure